Combined optimisation of design and power management of the hydraulic hybrid propulsion system for the 6 × 6 medium truck. (7th October 2004) - Filipi, Z.; Louca, L.; Daran, B.; Lin, C.-C.; Yildir, U.; Wu, B.; Kokkolaras, M.; Assanis, D.; Peng, H.; Papalambros, P.; Stein, J.; Szkubiel, D.; et al.
Hybrid propulsion systems are one of the critical technologies on the roadmap to future ultra-efficient trucks. While there is a significant body of work related to hybrid passenger cars and light commercial trucks, there are many open issues related to hybridisation of heavier trucks intended for both on- and off-road use. This work addresses those questions through a systematic analysis of the proposed parallel hydraulic hybrid powertrain for the Family of Medium Tactical Vehicles (FMTV). A representative duty cycle for the FMTV is generated based on information about the typical vehicle mission. A methodology for sequential optimisation of hybrid propulsion and power management systems is applied to a hydraulic hybrid configuration with post-transmission motor location. This analysis is critical in evaluating the fuel economy and mobility potential of the hybrid propulsion system, as well as enhancing our understanding of the phenomena leading to predicted fuel economy values.